Gold eletrode modified by dicarboxyl-calix[4]arene as electrochemical sensing platform for detection of lead(II), nickel(II) and zinc(II) ions - Abdul Aziz, Siti Fatimah Nur (2017)
Persistent of heavy metal pollution in water samples is the most concerned issues in worldwide because of the toxicity effect that poses a major threat to all life of environments. Thus, this leads to development of a wide range of tools and techniques of sensing including conventional methods like atomic absorption spectroscopy (AAS) and inductively-coupled plasma mass spectroscopy (ICP-MS) which more tedious to handle. As an alternative way, analytical approach which able to offer simplicity and faster response was explored by development of electrochemical sensor with various type of modifier as the sensing interface to detect the heavy metal ions. In this project, a simple and highly sensitive of electrochemical technique was developed for the determination of heavy metal ions such as lead(II), nickel(II) and zinc(II) ions in water samples using calix[4]arene derivative. The calixarene compound was chosen to develop a sensor based on dicarboxyl-calix[4]arene modified on gold surface (COOH-C4 electrode) as it has been known as one of great metallic cation sensing receptor due to its ability to chelate with various ions. Initially, the gold surface was modified with 3-mercaptopropionic acid (MPA) using self-assembly technique (MPA/Au electrode). The subsequent modification of MPA/Au with dicarboxyl-calix[4]arene compound was carried out by crosslinking the carboxyl groups from MPA and dicarboxyl-calix[4]arene through linkers, namely ethylenediamine (EDA), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxy succinimide (NHS) via one-pot reaction. The modified electrodes were characterized using X-ray photoelectron spectroscopy (XPS) and fourier transform infrared spectroscopy (FTIR). The results indicated the confirmation of each stage of electrode modification. The electrochemical analyses of COOH-C4 electrode showed an enhanced of electrocatalytic activity and higher current towards analytes (Ni2+, Pb2+ and Zn2+), compared to bare gold surface and MPA/Au electrode. Under optimum conditions, the differential pulse voltammetry response of COOH-C4 displayed a wide linear response range from 0.28 - 2.5 mg/l for Pb2+ ion, 2.85 – 6.65 mg/l for Zn2+ ion and 0.13 -1.68 mg/l for Ni2+ ion with the detection of limit of 0.0062 mg/l, 1.5 mg/l, 0.34 mg/l, respectively. A simultaneous study using similar concentration of analytes was also done and as a result, the COOH-C4 electrode was found to be sensitive towards Pb(II) ions compared to the other metal ions. Due to poor peak separation and low R2 value (0.7646) of Zn(II) and Ni(II)ions, respectively, the LOD reading was only obtained for Pb(II) ion which at 0.01 mg/l. Furthermore, the fabricated electrode shows good selectivity towards the Pb2+ ion in presence of possible interfering species. The developed COOH-C4 electrode then was successfully applied to determine Pb2+ ion in river water. A satisfactory precision of relative standard deviation at 3.12% and acceptable recoveries of 92 % were obtained which demonstrated the potential of dicarboxyl-calix[4]arene modified on electrodes (COOH-C4 electrode) as heavy metals sensing.